Significados paleoambientais e paleoclimáticos dos Paleossolos : uma revisão - Pierini, Cristina (2010)
The majority of paleosols are described from continental deposits, most commonly from alluvial strata. In these continental records to much little is revealed of conditions between events of sedimentation. In alluvial sedimentary environments, a record of these conditions is not lost and gone forever. They may be interpreted from fossil soils formed on deposits of floods or others agents of deposition. Paleosols can be categorized according to the interplay among deposition, erosion, and the rate of pedogenesis when they formed. Paleosols can help to interpret the history of sediment deposition and the autogenic and allogenic processes that influenced a sedimentary basin. Paleosols are also helpful in stratigraphic studies, including sequence stratigraphic analyses. In addition to their stratigraphic applications, paleosols can be used to interpret landscapes of the past by analyzing paleosol-landscape associations at different spatial scales, ranging from local to basin-wide in scope. Ancient climatic conditions can be interpreted from modern soil analogs or by identifying particular pedogenic properties that modern studies show to have climatic significance. Stable carbon and oxygen isotopic composition are also used to interpret ancient climate. A variety of features of sequences of paleosols may provide quantifiable evidence of the causes and effects of paleoenvironmental change. Paleosols are abundant in some sequences and may provide a detail record of the past. The richness of this record reveals complexities which are fundamental to understanding the long-term accumulation of such sequences.